SISTEM AKUNTANSI KEUANGAN DAERAH, KOMPETENSI SDM DAN AUDIT INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Aryani, Wiwin; Widodo, Tri; Puspita, Maria Entina (ITB AAS Indonesia Surakarta, 2024)
The research aims to determine the effect of implementing a regional financial accounting system, human resource competency and implementing internal audit on the quality of the Salatiga City regional government's financial reports. The population was 52 financial management employees in the Salatiga City Regional Government and were used as research samples. Explanatory research using data analysis methods, validity test, reliability test, multiple linear regression analysis test, t test, F test and coefficient of determination test. The partial research results show that the Regional Financial Accounting System has a positive and significant influence on the Quality of Salatiga City Regional Government Financial Reports, Human Resources Competency (HR) has a positive and significant influence on the Quality of Salatiga City Regional Government Financial Reports and Internal Audit has a positive and significant influence on the Quality of Salatiga City Regional Government Financial Reports. The Regional Financial Accounting System, Human Resources Competency, Internal Audit simultaneously contribute to the Regional Financial Quality of the Salatiga City Government by 40.6%, while the remaining 59.4% is influenced by other variables not examined in this research, namely the Use of Technology and Systems Internal control.